Transport of paclitaxel (Taxol) across the blood-brain barrier in vitro and in vivo - Fellner, Stephan; Bauer, Björn; Graeff, Claudia; Fricker, Gert (The journal of clinical investigation, 2002)
Paclitaxel concentrations in the brain are very low after intravenous injection. Since paclitaxel is excluded from some tumors by p-glycoprotein (p-gp), the same mechanism may prevent entry into the brain. In vitro, paclitaxel transport was examined in capillaries from rat brains by confocal microscopy using BODIPY Fl-paclitaxel. Western blots and immunostaining demonstrated apical expression of p-gp in isolated endothelial cells, vessels, and tissue. Secretion of BODIPY Fl-paclitaxel into capillary lumens was specific and energy-dependent. Steady state luminal fluorescence significantly exceeded cellular fluorescence and was reduced by NaCN, paclitaxel, and SDZ PSC-833 (valspodar), a p-gp blocker. Leukotriene C4 (LTC4), an Mrp2-substrate, had no effect. Luminal accumulation of NBDL-cyclosporin, a p-gp substrate, was inhibited by paclitaxel. In vivo, paclitaxel levels in the brain, liver, kidney, and plasma of nude mice were determined after intravenous injection. Co-administration of valspodar led to increased paclitaxel levels in brains compared to monotherapy. Therapeutic relevance was proven for nude mice with implanted intracerebral human U-118 MG glioblastoma. Whereas paclitaxel did not affect tumor volume, co-administration of paclitaxel (intravenous) and PSC833 (peroral) reduced tumor volume by 90%. Thus, p-gp is an important obstacle preventing paclitaxel entry into the brain, and inhibition of this transporter allows the drug to reach sensitive tumors within the CNS.